Market math : 50 ingredients x 4 recipes = 200 simple, creative dishes - Food & Wine Books (New York : Time Inc. Affluent Media Group, 2015)
Provides recipes for over two hundred dishes using the same fifty everyday ingredients, and includes recipes for such meals as avocado tartare, lemony tuna and artichoke dip, corn-shrimp dumplings, mixed bell pepper pasta, and turkey curry soup.
"Food & Wine Books."
"Based on Food & Wine magazine's beloved Market Math column"--Page 4 of cover.
Includes index.
Keywords: Cooking; Cooking; Cookbooks; Cookbooks